Islamic Compensation Concept: The Consumer Dispute Settlement Pattern in Indonesia - Holijah, Holijah; Rizal, M. (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
This article aims to explain the compensation concept in Islamic Law by emphasizing consumer law on the development of consumer dispute settlement patterns in Indonesia. In constructing a consumer dispute settlement pattern in demanding compensation to the produces as stipulated in the Law of the Republic of Indonesia Number 8 the Year 1999 concerning Consumer Protection Act, in order to be able to realize the providing Islamic compensation pattern that becomes the basis of the consumer dispute settlement pattern in Indonesia in the future. This research is a juridical normative with a legal approach and conceptual approach as well as a socio-legal approach. The research analysis used the descriptive qualitative analysis method. The results of this study indicate that the importance of the compensation concept in Islamic law is inseparable from observing the development diversification of goods and services products from the existence of free trade dynamics currently that is so advantageous to the consumers, although the tendency to be disadvantaged is also getting bigger. Losses that were experienced by consumers due to the weak position of consumers in various factors compared to produces. While the birth of Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection Act as the formality legal of consumer protection law in Indonesia will not rule out the possibility of other regulations in the field of consumer protection, so the alternatives development in providing consumer protection is crucial to be able to provide consumer protection that brings benefits and supports the national economy.